Desarrollo de un modelo matemático de optimización para el despacho económico mediante penetración de energía renovable no convencional . - Jaya Carvajal, Angel Fernando (2021)
Today in power systems the use of Non-Conventional Renewable Energies (NCRE) such as solar and wind is being implemented in order to reduce the CO2 emissions produced by generating electricity through fuel-based plants fossil. One of the disadvantages of using this type of unconventional energy is the randomness of wind speed and solar radiation, which makes it difficult to program an optimal economic dispatch in advance. For which the use of high-speed algorithms is essential. The present work is based on the development of a mathematical model for optimal power generation, in order to minimize operating costs and the consumption of fossil fuel (diesel) in an isolated Microgrid. The main objective is the development of a mathematical optimization model for the economic dispatch of a system made up of: NCRE (solar and wind), diesel generation, a storage system (batteries) and electricity demand, which are evaluated in a period time of 168 hours (1 week), to solve this optimization problem we used Mixed Integer Linear Programming (MILP). The mathematical model proposed is evaluated through the FICO EXPRESS OPTIMIZATION SUITE optimization program and a case study, in which it is observed that the electricity generation technologies cover the demand satisfactorily with the following percentages: solar energy 60,27%, diesel generation 10,48%, BESS 26,84% and wind energy 2,41%.